Europe and the Gospel. Past Influences, Current Developments, Mission Challenges - Van de Poll, Evert (De Gruyter, 2013)
Combining human interest stories with thought provoking analyses, Dr Evert Van de Poll paints the socio-cultural and religious picture of this exceptional continent: its population and cultural variety; past and present idea of 'we Europeans'; immigration, multiculturalism and the issue of (Muslim) integration; the construction of the EU and the concerns it raises; and the quest for the 'soul' of Europe. Special attention is paid to Christian and other roots of Europe; the mixed historical record of Christianity; vestiges of its past dominance; its place and influence in today's societies that are rapidly de-Christianising; and secularization as a European phenomenon. The author indicates specific challenges for Church development, mission and social service. In so doing, he outlines the contours of a contextualised communication of the Gospel.